This is a homework question

Prove if $\lim\limits_{n\rightarrow\infty}(a_1+a_2+...+a_n)=S$, then $\lim\limits_{n\rightarrow\infty}\frac{a_1+2a_2+...+na_n}{n}=0$

And this is my try to prove it,

Let $k < n$,


There are k zeros, and they are finite. So $\lim\limits_{n\rightarrow\infty}\frac{a_1+2a_2+...+ka_k}{n}=0$

Then, let $k\rightarrow\infty$, we get $$\begin{align*}\lim\limits_{k\rightarrow\infty}\left(\lim\limits_{n\rightarrow\infty}\frac{a_1+2a_2+...+ka_k}{n}\right)&=\lim\limits_{k\rightarrow\infty}0\\&=0\end{align*}$$

which equals to $$\lim\limits_{n\rightarrow\infty}\frac{a_1+2a_2+...+na_n}{n}=0$$

I'm not quite sure it's a correct proof. Especially, the step of letting $k < n$, I can't say that on what degree k is to be smaller than n. Since $n\rightarrow\infty$, then $k$ could also approach to $\infty$.

If it's not a valid proof, where goes wrong?

And I believe there are some better methods to prove it, please give me some hints.

Any suggestion will be appreciated.

  • $\begingroup$ is this graded homework? $\endgroup$ Commented Oct 21, 2015 at 3:49
  • $\begingroup$ No, it's just for practice. $\endgroup$
    – Cocoa
    Commented Oct 21, 2015 at 3:51
  • $\begingroup$ ah good, I would say your method doesn't work because you're trying to split it up in an unnatural manner where it seems more forced than logical. $\endgroup$ Commented Oct 21, 2015 at 3:53
  • $\begingroup$ Yes, I also got this feeling when I wrote it. If let $S_n = \sum\limits_{n\rightarrow\infty}a_n$, then rewrite the equation as $\lim\limits_{n\rightarrow\infty}\frac{nS_n-S_1-S_2-...-S_{n-1}}{n}$, so it's equal to $S_n-\lim\limits_{n\rightarrow\infty}\frac{S_1+S_2+...+S_{n-1}}{n}$. Can we say $S_n=\lim\limits_{n\rightarrow\infty}S_{n-1}=0$? $\endgroup$
    – Cocoa
    Commented Oct 21, 2015 at 4:01
  • 1
    $\begingroup$ Hint: use that if $\sum a_n $ converges, then $\lim_{n\to \infty }a_n=0$ $\endgroup$ Commented Oct 21, 2015 at 4:05

1 Answer 1


Well this is obvious if one uses the following result

Theorem: If $u_{n} \to L$ as $n \to \infty$ then $$\lim_{n \to \infty}\frac{u_{1} + u_{2} + \cdots + u_{n}}{n} = L$$

For the current question let $$S_{n} = a_{1} + a_{2} + \cdots + a_{n}$$ and we are given that $S_{n} \to S$ as $n \to \infty$. We have clearly $$a_{n} = S_{n} - S_{n - 1}, n > 1, a_{1} = S_{1}$$ and therefore \begin{align} b_{n} &= \frac{a_{1} + 2a_{2} + \cdots + na_{n}}{n}\notag\\ &= \frac{S_{1} + 2(S_{2} - S_{1}) + \cdots + n(S_{n} - S_{n - 1})}{n}\notag\\ &= \frac{nS_{n} - (S_{1} + S_{2} + \cdots + S_{n - 1})}{n}\notag\\ &= \frac{(n + 1)S_{n} - (S_{1} + S_{2} + \cdots + S_{n})}{n}\notag\\ &= \frac{n + 1}{n}\cdot S_{n} - \frac{S_{1} + S_{2} + \cdots + S_{n}}{n}\notag\\ &\to S - S = 0\text{ as }n \to \infty\notag \end{align}

Note: The theorem mentioned in the beginning is not obvious and its proof (although not too difficult) is available on MSE.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .